ER sensing of lipid metabolism drives PRA family-dependent regulation of COPII vesicle transport - Nakazato, Mitsuki; Nakamura, Hiroki; Kato, Mei; Ikema, Ryoko; Iguchi, Mizuki; Hanaoka, Kazuki; Eto, Katsuki; Karashima, Takefumi; Ikeda, Atsuko; Yabuki, Yukari; Schlarmann, Philipp; Manzano-Lopez, Javier; et al. (bioRxiv, 2024)
Newly synthesized secretory proteins and many lipids are transported from the endoplasmic reticulum (ER) to the Golgi prior to their ultimate destinations. The ER-to-Golgi transport must be tightly regulated during adaptation to environmental stress. However, the sensing mechanism and regulatory pathways governing the consecutive formation, budding and transportation of COPII vesicles from the ER remain insufficiently explored. Here, we present evidence indicating that COPII-mediated vesicle transport is transcriptionally controlled through the phosphatidic acid-dependent Opi1-Ino2/Ino4 regulatory circuit. Our analysis indicates that YIP3, a target gene of Ino2/Ino4, exerts a negative regulatory impact on COPII-mediated vesicle transport. Furthermore, we demonstrated that Ino2/Ino4 but not Yip3 modulates Sar1 activation, the initial step in COPII vesicle formation, whereas Yip3 hinders Sec16 assembly on the ER membrane, thereby implying that Ino2/Ino4 governs COPII-mediated trafficking at multiple steps. Thus, this study provides the first evidence for an ER sensing system that transcriptionally fine-tunes multiple steps of anterograde vesicular transport in response to alterations in lipid composition of the ER membrane.